The Effects of Audible Sound for Enhancing the Growth Rate of Microalgae Haematococcus pluvialis in Vegetative Stage - Marcelinus Christwardana; H. Hadiyanto (Bogor Agricultural University, Indonesia, 2017)
Physico-stimulant like audible sound is one of the new promising methods for enhancing microalgae growth rate. Here, microalgae Haematococcus pluvialis was cultivated with the addition of audible sound with titles “Blues for Elle” and “Far and Wide.” The objective of this research was to evaluate the effect of audible sound to the growth and productivity of microalgae. The experiment has been conducted by exposing the audible sound for 8 h in 22 days to microalgae cultivation. The result showed that microalgae H. pluvialis treated by the music “Blues for Elle” shows the highest growth rate (0.03 per day), and 58% higher than the one without audible sound. The average number of cells in stationary phase is 0.76 × 104 cells/mL culture and the productivity is 3.467 × 102 cells/mL/day. The pH of microalgae medium slightly decreases because of proton production during photosynthesisprocess. The kinetic rate constant (kapp) is 0.078 per day, reaction half-life (t1/2) is 8.89 days, and catalytic surface (Ksurf) is 1.66 × 10−5/day/cm2. In conclusion, this audible sound is very useful to stimulate microalgae growth rate, especially H. pluvialis.